The Effect of User Experience and Usability on User Satisfaction and Continuance Intention in the JConnect Mobile Application - Novita Khasanah; Faris Mushlihul Amin; Andhy Permadi (TIERS Information Technology Journal, 2023)
Technological innovation has developed in several sectors of society, such as banking. Banking digitalization in Indonesia has increased by 46.72% in 2022. With this increase, every bank will continue to strive for the quality of its mobile banking services in order to improve optimal and effective service for its customers. PT BPD East Java made similar efforts to improve digital banking branding services by launching JConnect Mobile. However, based on data, the JConnect Mobile application received a low rating, namely 3.2. From this data, it is necessary to evaluate the user experience and usability, there is user satisfaction and sustainable intentions to support the projection and direction of user satisfaction or sustainable intentions. Therefore, the aim of this research is to measure the level of evaluation of user experience and usability and its influence on user satisfaction and continuance intention. The indicators used to measure user experience and usability are the UEQ and SUS methods. This research uses a quantitative approach with linear regression analysis. Of the 8 hypotheses proposed, 3 hypotheses were rejected and 5 hypotheses were accepted. So it can be concluded that the aspects that influence user satisfaction and continuance intention are perspicuity, efficiency, novelty and usability.